Teach Beyond Boundaries: The Conceptual Framework and Learning Philosophy of an Innovative Initial Teacher Education Programme in Wales. (1st March 2020) - Thomas, Malcolm; Rees, Barry; Evans, Gareth Emyr; Thomas, Nicola; Williams, Clive; Lewis, Berian; Phillips, Daryl; Hand, Allyson; Bowen, Siân; Davies, Andrew; Davies, Prysor Mason; Chapman, Susan; et al.
This paper outlines the development of one integrated ITE programme that leads to two QTS pathways: Primary Post-Graduate Certificate in Education with Secondary Enrichment; and Secondary Post-Graduate Certificate in Education with Primary Enrichment. The integrated ITE programme AberTeach + enables student teachers to 'Teach beyond boundaries for an all-through experience'. This paper reviews the programme's conceptual framework and learning philosophy and in so doing, considers the core principles that influenced the design of the programme, as follows: Inclusive Partnership; Effective Pedagogy; Integrated Pedagogy; Specialised and Enriched Pedagogy; Shared and Reflective Pedagogy; Truly Collaborative Research Culture, Democratic Accountability and the eight principles of the Learning Philosophy. The paper proceeds to explain how the integrated programme is delivered via a cluster hub approach across 5 hub regions in Mid-Wales. In doing so, it outlines the role of the University staff and Lead and Partner school mentors as well as the minimum expectations for student teachers whilst on school experience. Consideration is also given to Welsh-medium provision and support as well as the centrality of research within the ITE Partnership as a whole. The paper closes by considering what is innovative about the programme and the benefits that student teachers gain from undertaking the programme.